Atomic/molecular layer deposition of cerium(iii) hybrid thin films using rigid organic precursors. Issue 14 (22nd March 2022) - Kaur, Parmish; Muriqi, Arbresha; Wree, Jan-Lucas; Ghiyasi, Ramin; Safdar, Muhammad; Nolan, Michael; Karppinen, Maarit; Devi, Anjana
Abstract : New ALD/MLD processes for Ce-based hybrid thin films using compatible inorganic and organic precursors with findings supported by DFT studies. Abstract : An atomic/molecular layer deposition (ALD/MLD) process for the fabrication of cerium-based metal–organic hybrid films is demonstrated for the first time. The highly reactive cerium(iii ) guanidinate precursor [Ce(dpdmg)3 ] was employed in combination with organic precursors composed of rigid backbones, terephthalic acid (TPA) and hydroquinone (HQ) for the growth of the respective hybrid films. Growth rates of the films as high as 5.4 Å per cycle for Ce-TPA and 4.8 Å per cycle for Ce-HQ at a deposition temperature of 200 °C were obtained. Density functional theory (DFT) investigations confirm the favorable interaction between the cerium precursor and the organic co-reactants and predict that Ce maintains its +3 oxidation state in the films. This was also confirmed experimentally by X-ray photoelectron spectroscopy (XPS). Additionally, the films are highly UV absorbing. Hence, we envision that these films could find future application as promising redox active materials and/or UV absorbing materials.